THE EFFECT OF A 6-WEEK INDIVIDUAL ANAEROBIC THRESHOLD BASED PROGRAMME IN A TRADITIONAL ROWING CREW - Gaizka Mejuto; Iñaki Arratibel; Jesús Cámara; Asier Puente; Gorka Iturriaga; Julio Calleja-González (Termedia Publishing House, 2012)
The purpose of the present study was to analyse a 6-week IAT (individual anaerobic threshold) based work load programme in a subelite rowing crew. 15 male rowers performed a 6-week IAT based work load distributed in 2, 2, 3, 3, 3, 2 sessions per week. To assess each rower's IAT training zone, the Stegmann method (22) was used. This training programme was framed in the 6-week precompetitive mesocycle (specific training period). Before and after this training programme the crew was tested in order to analyse the effects of the IAT stimuli programme. These tests were conducted at a starting work load of 100 W and increased by 40 W every 2 min until volitional exhaution. An improvement was found in cardiovascular efficiency and blood lactate concentration ([LA]) buffering capacity during all the work loads in the post-IAT training programme test (100, 140, 180, 220 and 260 W) (p<0.05). After 3 min recovery, significant differences were not observed in [LA] (NS). We conclude that the proposed training programme improves cardiovascular efficiency and [LA] buffering capacities but not the short-term recovery in a subelite traditional rowing crew.